2017
DOI: 10.1111/cogs.12529
|View full text |Cite
|
Sign up to set email alerts
|

Social Beliefs and Visual Attention: How the Social Relevance of a Cue Influences Spatial Orienting

Abstract: We are highly tuned to each other's visual attention. Perceiving the eye or hand movements of another person can influence the timing of a saccade or the reach of our own. However, the explanation for such spatial orienting in interpersonal contexts remains disputed. Is it due to the social appearance of the cue—a hand or an eye—or due to its social relevance—a cue that is connected to another person with attentional and intentional states? We developed an interpersonal version of the Posner spatial cueing par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 92 publications
(110 reference statements)
9
35
0
Order By: Relevance
“…This replicates findings from previous studies showing that even very basic social-cognitive processes like gaze cueing can be top-down modulated by social context information [53], and highlights that certain top-down modulators, such as the physical appearance of an agent, might only exert their effect in relatively lifelike interactions. This observation also provides some clarity regarding the ongoing debate in the literature whether manipulations related to mind perception and/or mentalizing have an effect on social attention [54] or not [55]. The current study suggests that there is an interaction between top-down and bottom-up mechanisms influencing social attention, but that the topdown component might only take effect in sufficiently realistic paradigms (see also [56]).…”
Section: Discussionsupporting
confidence: 55%
“…This replicates findings from previous studies showing that even very basic social-cognitive processes like gaze cueing can be top-down modulated by social context information [53], and highlights that certain top-down modulators, such as the physical appearance of an agent, might only exert their effect in relatively lifelike interactions. This observation also provides some clarity regarding the ongoing debate in the literature whether manipulations related to mind perception and/or mentalizing have an effect on social attention [54] or not [55]. The current study suggests that there is an interaction between top-down and bottom-up mechanisms influencing social attention, but that the topdown component might only take effect in sufficiently realistic paradigms (see also [56]).…”
Section: Discussionsupporting
confidence: 55%
“…However, interpretive processes also act on evaluative processes. For example, Gobel and colleagues have shown that others’ social rank boosts social orienting only when participants perceived the other agent as a human social partner with whom they were interacting on the same task as opposed to a computer‐delivered cue or a human agent engaged on a different task . Additionally, the same authors reported that the belief of being looked back at has an ability to reverse the preferential responding to high‐status individuals.…”
Section: The Relationship Between the Three Core Processesmentioning
confidence: 99%
“…mind ratings increase as a function of physical human-likeness [36,[92][93][94]), which allows us to experimentally manipulate mind perception via physical human-likeness. Second, because mind perception increases activation in social brain networks [52,[95][96][97] and has been shown to modulate social-cognitive processes like gaze cueing on a behavioural level [69,98], using tDCS in the context of a social attention paradigm seems suitable to investigate the outlined research goal. Left prefrontal and left temporoparietal areas were chosen as sites for tDCS stimulation for the following reasons: first, both areas have been implicated in mind perception in previous studies [28,32,34,51,53], and activation in both areas has been shown to correlate with variations in social attention (i.e.…”
Section: Introductionmentioning
confidence: 99%